2021
DOI: 10.1186/s13765-021-00625-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of proteins, lipids, and metabolites in two organic fertilizer products derived from different nutrient sources

Abstract: The biochemical composition of organic fertilizers largely determines their nutrient supply characteristics following soil application as well as their potential impact on soil microbial communities. Yet, limited information is available regarding the biochemical composition of organic fertilizers derived from different nutrient sources. Here, we qualitatively analyzed the presence and abundance of proteins, lipids, and metabolites in a liquid fish fertilizer (LFF) product and a type of granular organic fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…In this study, the granular organic fertilizer was primarily derived from hydrolyzed feather, bone, and blood meal, whereas the liquid organic fertilizer was derived from enzymatically digested fish proteins. As pointed out by Li et al (2021b), the slower release of N from the granular organic fertilizer may be associated with the presence of complex proteins and long-chain saturated fatty acids. Hartz and Johnstone (2006) compared the N availability of different types of organic fertilizers and found the N mineralization from the fish powder was significantly higher than that of blood meal, feather meal, and seabird guano within the first week at 10, 15, or 20 C. However, after 2 weeks, the mineralization of all fertilizers slowed down, highlighting the need for split applications of organic fertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the granular organic fertilizer was primarily derived from hydrolyzed feather, bone, and blood meal, whereas the liquid organic fertilizer was derived from enzymatically digested fish proteins. As pointed out by Li et al (2021b), the slower release of N from the granular organic fertilizer may be associated with the presence of complex proteins and long-chain saturated fatty acids. Hartz and Johnstone (2006) compared the N availability of different types of organic fertilizers and found the N mineralization from the fish powder was significantly higher than that of blood meal, feather meal, and seabird guano within the first week at 10, 15, or 20 C. However, after 2 weeks, the mineralization of all fertilizers slowed down, highlighting the need for split applications of organic fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…These results were possibly associated with the residual nutrients from the previous crop season and reflected the long-term or legacy impact of cover cropping and organic fertilizer and compost application because no nutrient sources were applied during the catch crop season. Given that the composition of different organic fertilizers (Li et al 2021b) and cover crops (Woodruff et al 2018) may determine their shorter-and longer-term nutrient availability, it is likely that different organic fertilizer and cover crop combinations could show differential impacts on nutrient supply to vegetable crops, together with the site-specific environmental effects. Interestingly, the cover crop × fertilization × compost interaction on the first harvest of lettuce in Year 3 also indicated that Yard and Cow further enhanced crop yield of the Cowpea 1 Liquid combination compared with NC, but the compost effect was lacking in other cover crop and fertilization combinations (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation